Implementation of Islamic Business Ethics in Micro, Small, and Medium Enterprises (MSMEs) in Surabaya - Qonita Shofiyani; Abdur Rohman (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
Abstract. This study explores the implementation of Islamic business ethics among Micro, Small, and Medium Enterprises (MSMEs) in Surabaya. Using a qualitative method with a literature review approach, this research identifies how MSME actors apply Islamic ethical principles such as unity (tawhid), justice ('adl), honesty (ṣidq), responsibility (amanah), and free will in daily business activities. The findings show that several MSMEs have adopted sharia-based business practices, including lawful contracts, fair pricing, transparency, and consumer protection. The integration of e-commerce and digital entrepreneurship is also aligned with Islamic values, supporting both business growth and ethical compliance. However, challenges remain, particularly in the consistent application of honesty and ethical awareness among traders. This study concludes that fostering an Islamic ethical business environment among MSMEs requires collaborative efforts from entrepreneurs, educational institutions, and government support to build a sustainable, fair, and value-based economic ecosystem.